Age-Related Changes in Standing Balance in Preschoolers Using Traditional and Nonlinear Methods - Hao, Zengming; Yang, Yi; Hua, Anke; Gao, Ying; Wang, Jian (Frontiers in Physiology, 2021)
Considerable disagreement exists on the linearity of the development of standing balance in children. This study aimed to use different traditional and nonlinear methods to investigate age-related changes in standing balance in preschoolers. A sample of 118 preschoolers took part in this study. A force platform was used to record the center of pressure during standing balance over 15 seconds in three conditions: eyes open, eyes closed, and/or head extended backward. Detrended fluctuation analysis (DFA), recurrence quantification analysis (RQA), and traditional measures were used to evaluate standing balance. The main results are as follows: (1) higher range and standard deviation in the anterior-posterior direction were observed for 5-year-old than for 4-year-old children, while higher DFA coefficient (at shorter time scales) and higher determinism and laminarity in the anterior-posterior direction were found for 5-year-old children compared to 3- and 4-year-old children; (2) as sensory conditions became more challenging, all traditional measures increased and DFA coefficients (at shorter and longer time scales) decreased in the anterior-posterior and mediolateral directions, while determinism and laminarity significantly declined in the anterior-posterior direction. In conclusion, although increased postural sway, 5-year-old preschool children's balance performance improved, and their control strategy changed significantly compared with the younger preschoolers. Sensory perturbation (eye closure and/or head extension) changed preschoolers’ balance performance and control strategy. Moreover, both traditional and nonlinear methods provided complementary information on the control of standing balance in preschoolers.